GLORIFICATION OF LOCAL CULTURAL WISDOM IN THE IMPLEMENTATION OF FLS2N IN THE FIELD OF CREATIVE DANCE - Sunaryo, Ayo; Hapidzin, Rivaldi Indra; Dyani, Putri Lilis; Santana, Fifiet Dwi Tresna (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
This scientific article aims to create creative dance works based on the local cultural wisdom of West Java, specifically Sukabumi Regency, for the FLS2N competition. The organization of FLS2N at the high school level is an effort to develop the artistic spirit of elementary school students. Through FLS2N at the high school level, a love for the arts will be fostered, which will inspire them to preserve Indonesian art and protect the nation's cultural heritage, based on the local cultural wisdom of each region. The method used is action research. Through a qualitative paradigm, this method is used to describe data in an actual, realistic, and systematic manner in creating dance works for FLS2N needs. Data collection is conducted through interviews, participatory observation, document studies, focus group discussions, and reflection. The results of the study show that art and culture teachers in Sukabumi Regency can enhance their understanding and skills in creating creative dance works for FLS2N at the high school/MA level based on local cultural wisdom. Keywords: Breeding, Local Cultural Wisdom, FLS2N